2022
DOI: 10.21315/aamj2022.27.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Leader-member exchange and creative idea validation: The role of helping and bullying

Abstract: The purpose of this paper is to explore the role of leader-member exchange (LMX) for selection-focused creativity. Thus, we seek to understand when subordinates develop high- quality relationships with their supervisors, do they also get their creative ideas validated by co-workers or not? The proposed model was tested using data obtained at two points in time from three data sources (co-workers, subordinates, and supervisors) working at a software solution provider operating in Pakistan. The obtained data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In other words, endorsing idea sharing is comparatively more complicated in contrast to fostering other discretionary behaviors such as organizational citizenship behavior. The studies conducted in the recent times, such as [ 71 ], have analyzed the factors that facilitate information and idea sharing at the workplace. Even though a large number of studies have agreed that leaders play an important role in boosting employees' enthusiasm to exchange ideas, there is limited research analyzing the effects of negative leadership behaviors such as abusive supervision on the creativity-sharing phenomenon.…”
Section: Research Contributionsmentioning
confidence: 99%
“…In other words, endorsing idea sharing is comparatively more complicated in contrast to fostering other discretionary behaviors such as organizational citizenship behavior. The studies conducted in the recent times, such as [ 71 ], have analyzed the factors that facilitate information and idea sharing at the workplace. Even though a large number of studies have agreed that leaders play an important role in boosting employees' enthusiasm to exchange ideas, there is limited research analyzing the effects of negative leadership behaviors such as abusive supervision on the creativity-sharing phenomenon.…”
Section: Research Contributionsmentioning
confidence: 99%
“…For certain individuals as well as positions, creativity stands as a prime goal [ 32 , 92 ], while for others, it is neither anticipated nor promoted; in such environments, it may even be prohibited [ 37 , 93 ]. Creative endeavors generally encourage autonomous motivation [ 40 , 94 ]. However, it is conceivable to feel autonomously driven while creativity is not anticipated and similarly feel unmotivated wherever creativity is a requisite [ 87 , 95 ].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Additionally, there exists growing proof that employees are likely to exhibit superior performance if trusting bonds exist with their managers (Graen & Uhl-Bien, 1995;Liden et al, 1997). Such enhancement takes place as a result of the fact that in an elevated LMX, supervisors give individuals extra assistance, perks, and chances for professional advancement (Adeel et al, 2022;Adeel, Pengcheng, Saleem, Ali, & Batool, 2019). Despite the widespread belief that employee voice improves work performance, factual research has found that this impact varies significantly (Burris, 2012;Hirschman, 1970).…”
Section: Employee Voice Lmx and Creative Idea Endorsementmentioning
confidence: 99%
“…Researchers observed that higher-ups were more likely to treat pre-emptive assisting action by employees more favorably when they linked it to altruistic intentions (Chen & Zhang, 2021). Similarly, studies discovered that higher-ups/ managers were more likely to support employees' opinions when they saw their roles as loyal rather than a danger (Adeel, Batool, Kee, Madni, & Khan, 2022;Burris, 2012). Such results imply that managers' reactions to employees' initiative approaches are influenced by their interpretation of those activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation